PAKET BUKU SAKU PRAMUKA PENGGALANG RAMU - Mita Septiani (Perspektif Ilmu Pendidikan, 2012)
Scouts’ program as extracurricular activities contribute positive values to the students. The scouts’ program should be implemented regularly, orderly, and continuously to attain the objectives. However, in fact number of scouts still do not have enough knowledge of the scout’s etiquette and skills. This research conducted at SDI Al Azhar 13 Rawamangun, Jakarta, from June through November 2011 aims at producing a pocket book for the scouts of penggalang ramu, employed development method of Rowntree. The try out of the product was done by expert review, face-to-face and filed trials. The research produced a a pocket book for scout of penggalang ramu ro be used to improve thescouths’ knowledge and skiils.